ANALISIS PEGARUH DIGITAL MARKETING DAN LAYANAN CASH ON DELIVERY (COD) TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Konsumen E-Commerce Shopee di Kota Semarang) - Feriyanto, Agus; Indriyatni, Lies (STIE PENA, 2025)
AbstractThis study aims to determine the influence of Digital Marketing and Cash On Delivery (Cod) Services on Trust as an Intervening Variable in Shopee E-Commerce Consumers in Semarang City. The sample of this study was 114 people with a non-probability sampling technique with a purposive sampling approach, namely the researcher subjectively selected the purposive sample. The method of data collection is with a questionnaire distributed through google forms. The types of data used are primary data and secondary data. The research method used in this study is Path Analysis. The results of this study show that Digital Marketing has an effect on Trust and Cash On Delivery Service has an effect on Trust. Digital Marketing affects Purchase Decisions and Cash On Delivery Services do not affect Purchase Decisions. Digital Marketing and Cash On Delivery Services affect Purchase Decisions with Trust as an intervening variable for Shopee E-Commerce Consumers in Semarang City.Keywords: Digital Marketing, Cash On Delivery Services, Trust and Purchase Decisions.